Causas de morte numa unidade de internamento de agudos de psiquiatria de um hospital geral português - Barbosa, Sofia (2016)
Introduction: Psychiatric patients are at increased risk of death from a number of natural and unnatural causes. This study examines the mortality causes of all psychiatric inpatients of an acute psychiatric unit at a general hospital in Portugal for sixteen years (1998 to 2013). Material and Methods: Twenty-one inpatients died at the inpatient unit between 1998 and 2013 (average 1.3 per year). A retrospective study through case-file review was carried to collect demographic characteristics, medical and psychiatry diagnosis. Patients transferred to other wards during their admission were not included. Results: Circulatory system diseases were the most prevalent causes of death, occurring in 2/3 of patients and include pulmonary embolism (n = 6), acute stroke (n = 3), cardiac arrhythmia (n = 2), acute myocardial infarction (n = 1), abdominal aortic aneurysm rupture (n = 1) and heart failure (n = 1). Two patients died with pneumonia and in four cases the cause of death was undetermined. Only one case of suicide was registered. Discussion: Circulatory conditions were the most frequent causes of death in our inpatient unit. Albeit a relatively rare event, inpatient suicide does occur and, in addition to its complex consequences on staff, family and patients should remain a focus for continued prevention. Conclusion: Mortality studies are important for determining quality of health care and to create recommendations for preventive measures.